Numerical Simulation on Mechanical Strength of a Wooden Golf Stick - Darianto, Darianto; Umroh, Bobby; Amrinsyah, Amrinsyah; zulfikar, zulfikar (JOURNAL OF MECHANICAL ENGINEERING, MANUFACTURES, MATERIALS AND ENERGY, 2018)
In general, golf players only know the techniques used in Golf games, but do not know the golf sticks response that occurs when the ball is hit. Referred to as response is the stress and strain that arises from the impact load that occurs when the hitting member touches the ball. The objectives of this research are: (a) to analyze golf sticks response when impact occurs, and (2) to know the stress distribution that occurs in golf sticks. The golf stick design in this study uses the autodesk inventor software. The material used is Titanium for head stick and Graphite for stick rod. The basic principle of this study is based on simple swing pendulum method. The variables that will be used for simulation are: swing speed, that is difference between start and end speed, that is Îv = 272,2 m / s, impact time, which is the time when the ball touches the batter Ît = 0.0005 seconds, the volume of the head of the stick Vo = 96,727 mm3, the cross-sectional area of the stick A = 63,504 mm2, the head mass of the sticks Ï = 4620 kg / m3, and the modulus of titanium elasticity 9.6 e +10 Pa. From the simulation result on the surface of the golf club hitter is obtained as follows: Ïmax = 2.1231e +10 Pa at 1.231e-06 s, emax = 0.22115 m / m at 1.231e-06 s, and the maximum stress and strain is located in the area the connection between the stick and the head of the stick.